Reflective study: pedagogical experiences and socialized method in higher education - Cuéllar Juárez, David Saúl; Sánchez Aguirre, Flor de María; Alcaide Aranda, Lourdes Ivonne del Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of the study was to systematize and analyze the theoretical review that supports the pedagogical experience and the socialized method of higher education students. The focus of the study was qualitative, type of research literature review, narrative design, considering similarity criteria in the various theories reviewed in high impact articles, in addition to using tree diagram strategies and the active research strategy (DIA). It is concluded that there is an incipient use of the socialized method; lack of self-reflection; little reflexive analysis in the pedagogical experience of the student of the initial teacher training (FID).